Effects of Pre-Storage Treatment with Ethanol and CO2 on Onion Dormancy - Qadir, Altaf; Hashinaga, Fumio; Karim, Md Rezaul (Journal of Bio-Science, 2009)
Onion (Allium cepa L.) cvs. âTazan' and âIyomante' were pre-treated either with ethanol (at a dose of 0.34, 0.68 and 0.91g.kg-1) and stored at 0, 10, 20 and 30ÂºC or with 100% CO2 (for 3.5, 7 and 14 days) and stored at 20ÂºC. Treatment of onion with ethanol delayed rooting, sprouting and reduced decay in both cultivars. Chemical analysis and organoleptic tests showed that the treatments had no adverse effect on the quality of onion. Pre-storage treatment with 100% CO2 for 3.5 and 7 days enhanced rooting and sprouting, while 14-days treatment exhibited a slight inhibitory effect. Key words: Onion, storage, ethanol, CO2 Â doi: 10.3329/jbs.v15i0.2203 J. bio-sci. 15: 55-62, 2007